THE EFFECTIVENESS OF USING ENGLISH SONGS AS WARMING UP ACTIVITY TO ENHANCE STUDENTS’ MOTIVATION IN ENGLISH CLASSROOM AT THE EIGHTH GRADE OF SMPN I ENOK - Hariyati; Agus Mustajib; Edi Ardian (Program Studi Pendidikan Bahasa Inggris, 2020)
Motivation is a factor which important in do something. For the Students, motivation is one factor that influences the teaching-learning process in the classroom. This time, motivation is a factor that becomes a problem for the students SMPN I Enok. This problem is the background of the problem in this research. To solve the students' motivation in the English classroom, the researcher conducted the experimental research with a quasi-experimental design with applying the English song as a warming-up activity to solve the problem. This research aimed to know the effectiveness of using English songs as a warming-up activity to enhance students' motivation in the English classroom at the eighth grade of SMPN I Enok. The data collection technique in this research was a questionnaire, and the instruments were 15 Close Ended statements using the Likert Scale type. This research sample was 50 students of the eighth-grade SMPN I Enok as a control and experimental class. After getting the data using the questionnaire, the researchers found that English song as warming up activity was useful to enhance students” motivation in English classroom with the result t-observed was 19,85 while t-table was 2,01 from 5% and 2,68 from 1%. The t-observed score was higher than the t-table. Based on the result, H0 (null hypothesis) is rejected, and H1 (alternative hypothesis) is accepted. It also means that English song as warming up activity was sufficient to enhance students' motivation in the English classroom at the eighth grade of SMPN I Enok in academic years 2018/2019.